Is Gender-Based Violence a Social Norm? Rethinking Power in a Popular Development Intervention. Issue 1 (November 2020) - Piedalue, Amy; Gilbertson, Amanda; Alexeyeff, Kalissa; Klein, Elise
Changing social norms has become the preferred approach in global efforts to prevent gender-based violence (GBV). In this article, we trace the rise of social norms within GBV-related policy and practice and their transformation from social processes that exist in the world to beliefs that exist in the minds of individuals. The analytic framework that underpins social norms approaches has been subject to ongoing critical revision but continues to have significant issues in its conceptualisation of power and its sidelining of the political economy. These issues are particularly apparent in the use of individualised measures of social norms that cannot demonstrate causation, and conflation of social norms with culture. Recognising that the pressure to measure may be a key factor in reducing the complexity of the social norms approach, we call for the use of mixed methods in documenting the factors and processes that contribute to GBV and the effectiveness of interventions. As social norms approaches are increasingly prioritised over addressing the non-normative contributors to GBV (such as access to and control over productive resources), awareness of the limitations of social norms approaches is vital.